Beam Profiling of Quantum Dot VCSEL for 10Gb/s Data Transmission - CHU, Y. (Institutional Knowledge at Singapore Management University, 2006)
Beam profiling of broad area quantum-dot VCSEL is presented with 10Gb/s data transmission over 300m of MMF. Single mode-performance with SMSR of 35dB is achieved with no significant impairment of the modulation performance.